On the taxonomy and distribution of Aphrodes bicincta (Schrank, 1776) species group (Homoptera: Auchenorrhyncha: Cicadellidae: Aphrodinae) in Eastern Palaearctic - Tishechkin, Dmitri Yu. (Zootaxa, 2017)
Two species from the Aphrodes bicincta group were revealed in the Eastern Palaearctic based on male calling signal analysis. A. bicincta = A. bicincta ferganensis Dubovsky, 1966 syn. n. was found only in Kazakhstan and Central Asia; in these regions it is sometimes sympatric with A. diminuta = A. centrorossica. A. diminuta occurs in Kazakhstan, Central Asia, Siberia, and the Russian Far East. Males of both species from the Eastern Palaearctic usually can be easily distinguished by the size, coloration, and penis shape. Also, despite the size differences from European specimens, the key from Bluemel et al. (2014) can be successfully used for their identification.